Perlindungan Hukum bagi Bidan Praktik Mandiri dalam Menjalankan Praktik Kebidanan - Rezky Fransilya Sumbung (Faculty of Law- Hang Tuah University, 2021)
Legal Protection for Practicing Midwives is regulated in Law Number 36 Year 2014 concerning to Health Workers, Articles 57 and 75. Article 57 stipulates that: